Distortion of athletic potential assessment in young football players under conditions of age-related heterogeneity - Korovin, T.D. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the features of distortion in the assessment of sporting potential of young football players under conditions of age-related heterogeneity and to substantiate the necessity of accounting for this factor when conducting sports selection. Methods and structure of the study. The empirical basis of the study comprised data from the official team rosters participating in the competition “Moscow City Football Championship among sports school teams ‘Club League’ of the 2026 season”. The study involved 1,261 football players born between 2012 and 2016, representing 14 leading football academies of Moscow. The analysis was conducted based on data from the Regional Public Organisation “Moscow Football Federation”. The study employed methods of statistical analysis, grouping and comparative assessment of the distribution of athletes by quarters of the calendar year. The methodological basis comprised provisions on the heterogeneity of biological development rates and their influence on the manifestation of motor abilities in the youth age group. Results and conclusions. A pronounced shift in the distribution of football players by birth quarters was established: the share of players born in the first quarter was 52.2%, while the share of fourth-quarter representatives was 8.4%. The identified disproportion indicates the presence of a systematic distortion in the sports selection procedure caused by age-related heterogeneity. It was shown that athletes with a higher level of morphofunctional development at the current stage gain an advantage, which leads to the underestimation of potentially promising players. The obtained results confirm the necessity of introducing organisational-methodological approaches oriented towards accounting for individual developmental rates and improving the objectivity of sporting potential assessment.